Measurement of Lateral Transmission of Force in the Extensor Digitorum Longus Muscle of Young and Old Mice - Keitaro Minato (MDPI AG, 2021)
The main function of skeletal muscles is to generate force. The force developed by myofiber contraction is transmitted to the tendon. There are two pathways of force transmission from myofibers to tendons: longitudinal transmission that depends on tension elicited via the myotendinous junction and lateral transmission that depends on shear elicited via the interface between the myofiber surface and surrounding connective tissue. Experiments using animal muscle and mathematical models indicated that lateral transmission is the dominant pathway in muscle force transmission. Studies using rat muscle showed that the efficiency of lateral force transmission declines with age. Here, the lateral transmission of force was measured using the extensor digitorum longus muscle from young and old mice. Dependence on longitudinal transmission increased in the old muscle, and there was a trend for lower efficiency of lateral force transmission in the old muscle compared to the young muscle. There was a noticeable increase in the connective tissue volume in the old muscle; however, there was no significant change in the expression of dystrophin, a critical molecule for the link between the myofiber cytoskeleton and extracellular matrix. This study demonstrates the measurement of lateral force transmission in mouse muscles and that alteration in force transmission property may underlie age-related muscle weakness.